2014
DOI: 10.1002/2014ja020114
|View full text |Cite
|
Sign up to set email alerts
|

GPS scintillation and irregularities at the front of an ionization tongue in the nightside polar ionosphere

Abstract: In this paper we study a tongue of ionization (TOI) on 31 October 2011 which stretched across the polar cap from the Canadian dayside sector to Svalbard in the nightside ionosphere. The TOI front arrived over Svalbard around 1930 UT. We have investigated GPS scintillation and irregularities in relation to this TOI front. This is the first study presenting such detailed multi‐instrument data of scintillation and irregularities in relation to a TOI front. Combining data from an all‐sky imager, the European Incoh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
59
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(64 citation statements)
references
References 102 publications
4
59
1
Order By: Relevance
“…The convecting patches develop intermediate-scale irregularities by action of the gradient-drift instability mechanism (Kersley et al 1995), that is also confirmed by numerical simulation (Gondarenko and Guzdar 2004). Because of the steep plasma density gradients and irregularities at their edges (Weber et al 1986), the TOI structure and polar cap patches can be detected with GPS measurements (e.g., Aarons 1997;Noja et al 2013;van der Meeren et al 2014). …”
Section: Resultsmentioning
confidence: 57%
“…The convecting patches develop intermediate-scale irregularities by action of the gradient-drift instability mechanism (Kersley et al 1995), that is also confirmed by numerical simulation (Gondarenko and Guzdar 2004). Because of the steep plasma density gradients and irregularities at their edges (Weber et al 1986), the TOI structure and polar cap patches can be detected with GPS measurements (e.g., Aarons 1997;Noja et al 2013;van der Meeren et al 2014). …”
Section: Resultsmentioning
confidence: 57%
“…This is mostly clear in the high-resolution (1s) σ ϕ data. The carrier phase measurement was detrended by first subtracting a fourth-order polynomial fit from the raw phase and then filtering the remainder using a high-pass Butterworth filter with a cutoff frequency of 0.2 Hz (van der Meeren et al, 2014). However, during the late phase of the RFE, the GPS phase scintillations enhanced abruptly.…”
Section: Bzmentioning
confidence: 99%
“…1). The GISTM receiver is a GSV 4004B model (Van Dierendonck and Arbesser-Rastburg, 2004), which is a NovAtel OEM4 dual-frequency receiver with special firmware specifically configured to measure and record power and phase of the GPS L1 signal at a high sampling rate (50 Hz). Each receiver is capable of tracking and reporting scintillation and total electron content (TEC) measurements simultaneously from up to 10 GPS satellites in view.…”
Section: Instruments and Datamentioning
confidence: 99%